2015
DOI: 10.1016/j.schres.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of early cortical processing and reading ability to functional status in individuals at clinical high risk for psychosis

Abstract: Background There is a growing recognition that individuals at clinical high risk need intervention for functional impairments, along with emerging psychosis, as the majority of clinical high risk (CHR) individuals show persistent deficits in social and role functioning regardless of transition to psychosis. Recent studies have demonstrated reduced reading ability as a potential cause of functional disability in schizophrenia, related to underlying deficits in generation of mismatch negativity (MMN). The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…This latter finding is consistent with numerous previous studies which have identified fMMN abnormalities in patients with chronic schizophrenia (See meta-analysis by Umbricht and Krljes, 2005). A few studies have also observed reduced fMMN in UHR when compared to healthy controls (Carrion et al, 2015;Perez et al, 2014). In light of the evidence for fMMN abnormalities in patients with long-term psychotic disorders, combined with the preliminary evidence for fMMN deficits in UHR individuals, the first aim of the current study was to investigate whether UHR individuals also exhibit fMMN deficits relative to healthy controls.…”
Section: Introductionsupporting
confidence: 92%
“…This latter finding is consistent with numerous previous studies which have identified fMMN abnormalities in patients with chronic schizophrenia (See meta-analysis by Umbricht and Krljes, 2005). A few studies have also observed reduced fMMN in UHR when compared to healthy controls (Carrion et al, 2015;Perez et al, 2014). In light of the evidence for fMMN abnormalities in patients with long-term psychotic disorders, combined with the preliminary evidence for fMMN deficits in UHR individuals, the first aim of the current study was to investigate whether UHR individuals also exhibit fMMN deficits relative to healthy controls.…”
Section: Introductionsupporting
confidence: 92%
“…In schizophrenia, these processes are impaired, leading to reduced sensitivity to ongoing environmental (auditory) events 10,94 . Deficits in MMN are highly interrelated to impaired functional outcome in schizophrenia, including impairments in reading 93 and educational achievement 32,167 . As opposed to behavioural measures that may be difficult to translate across species, MMN provides an objective neurophysiological measure that can be implemented in primates and/or rodents to investigate underlying neural mechanisms.…”
Section: Figurementioning
confidence: 99%
“…Among individuals showing subthreshold clinical symptoms of Sz, MMN has been found to predict the time to conversion to Sz . In addition, as in established Sz, deficits in MMN generation in patients at high clinical risk for Sz also correlate strongly with overall level of social and role function . Thus, agents capable of improving MMN deficits might be especially effective when instituted at early stages of the disorder.…”
Section: Mismatch Negativitymentioning
confidence: 99%